C-Reactive Protein/Albumin (Crp/Alb) Ratio as a Predictor of Ovarian Cancer - Budian Budiana; Bayu Mahendra; Putra Wiradnyana; Darmayasa Darmayasa; Fajar Marta; Suwanpramana Suwanpramana (Jurnal Health Sains, 2023)
Ovarian cancer is a type of cancer with a high incidence and mortality rate in Indonesia and worldwide. C-reactive protein (CRP) is an inflammatory marker meanwhile albumin is an indicator of nutritional deficiencies in ovarian cancer. This study is a diagnostic test for ovarian cancer in women aged >18 years and without previous history of ovarian cancer who underwent laparotomy or laparoscopy at Prof. Ngoerah General Hospital, Denpasar. Samples were taken by consecutive sampling. CRP examination was carried out in the laboratory by immunoturbidimetry method using the CRP Latex Kit (Roche) and measured using a Cobas integra 501 at a wavelength of 552 nm. The gold standard to diagnosed ovarian cancer was according to histopathological examination. A total of 69 women with ovarian tumors were recruited into the study which consisted of 40 ovarian cancers and 29 benign ovarian tumors. A significantly higher median CRP/Albumin ratio was found in ovarian cancer patients compared to benign ovarian tumors (6.9 vs 0.45; p=0.001). The optimal CRP/albumin ratio cut-off value was 1.34. The diagnostic capability of the CRP/Albumin ratio was found to be the best in diagnosing cancer at an advanced stage with a sensitivity of 86.9%, specificity of 68.9%, PPV of 68.9%, NPV of 86.9%, accuracy of 76.9%, positive likelihood ratio 2.8 and negative likelihood ratio 0.2. CRP/Albumin ratio can a potential diagnostic tool for ovarian cancer especially in advanced stage.